Phosphate removal from water by fly ash: Factorial experimental design - Can, Mevra Yalvac; Yildiz, Ergun (ELSEVIER, 2006)
The influence of three variables (phophate concentration, initial pH of solution (pH(0)) and the fly ash dosage) on the removal efficiency of phosphate (% E) and equilibrium pH of solution (pH(eq)) by using fly ash was studied by means of 2(3) full factorial experimental designs. The parameters coded as x(1), x(2) and X-3, consecutively. were used. The parameters were investigated at two levels (-1 and 1). The effects of these factors on dependent variables, namely. % E and pH,, were investigated. To determine the significance of effects. the analysis of variance with 95% confidence limits was used. It was shown that % E and pH,, obtained in this study were found to be 99.6% and 11.16, corresponding to the operating condition of 25 mg l(-1), 2 g l(-1) and 5.5 for the phosphate concentration. fly ash dosage and pH(0). respectively. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phosphate removal; fly ash; experimental design; factorial design; AQUEOUS-SOLUTIONS; HEAVY-METAL; SORPTION; ADSORPTION; COAL; Engineering; Environmental Sciences & Ecology